Internal Factors Affecting Perceived Impact of ICT on Rural Business Potential : The Mediating Role of Productive Internet Usage - Shahren Ahmad, Zaidi Adruce; Nur Adila, Latif (Asian Economic and Social Society (AESS), 2020)
This paper aims to find out the mediating effect of productive internet usage in the relationship between internal factors of internet adoption and perceived rural business potential impact of Information and Communication Technology (ICT). Internal factors investigated in this study are perceived ease of use of ICT, perceived usefulness of ICT, and ICT literacy. The expected outcome is perceived impact of ICT on rural business potential, while productive internet usage act as the mediator variable in this study. The findings show that productive internet usage mediates the effect of the three internal factors on the expected outcome. This study shows the important of creating more opportunity for the community members to get more exposure to the productive internet usage and its benefit, especially in increasing business potential. Besides that, through the mediation model analysis, this study helps to assess the effectiveness of internet usage for rural business potential and give an insight of how productive internet usage plays its role in mediating the impact of internal factors on the perceived impact of ICT on rural business potential.